Non-syndromic unilateral supplemental maxillary central incisor: a case report - Tangade, Pradeep; Batra, Manu; Ravishankar, T L; Amit, Tirth; Pal, Sumit (Ethiopian journal of health sciences, 2013)
Supernumerary teeth are developmental anomaly. There are various theories explaining their occurrence. Maxilla is more commonly affected and males have higher predilection than females for having supernumerary teeth. The present case is presented with three permanent central incisors, all of them with normal morphology. On clinical and radiographic examination, it was identified as a case of non-syndromic unilateral left supplemental maxillary central incisor. Treatment plan involved extraction of the supplemental tooth followed by orthodontic treatment to correct the malalignment of the teeth. The presence of supplemental teeth of normal morphology is quite a rare condition and are commonly associated with various syndromes but, in rare cases, they also exists as non-syndromic forms. Supernumerary teeth can cause aesthetic or functional problems, especially when situated in the maxillary anterior region. Complications related to the phenomenon can be minimized by early detection and by carrying out a comprehensive treatment protocol.